Impaired Emotional Learning and Involvement of the Corticotropin-Releasing Factor Signaling System in Patients with Irritable Bowel Syndrome - Labus, Jennifer S. (2013)
BACKGROUND & AIMS: Alterations in central corticotropin-releasing factor (CRF) signaling pathways have been implicated in the pathophysiology of anxiety disorders and irritable bowel syndrome (IBS). We aimed to characterize the effects of the CRF receptor 1 (CRF-R1) antagonist, GW876008, on brain and skin conductance responses (SCR) during acquisition and extinction of conditioned fear to the threat of abdominal pain in subjects with IBS and healthy individuals (controls). METHODS: We performed a single center, randomized, double-blind, 3-period crossover study of 11 women with IBS (35.50 ± 12.48 y old) and 15 healthy women (controls) given a single oral dose (20 or 200 mg) of the CRF-R1 antagonist or placebo. Blood-oxygen-level-dependent (BOLD) responses were analyzed using functional magnetic resonance imaging in a tertiary care setting. RESULTS: Controls had greater SCR during acquisition than extinction, validating the fear conditioning paradigm. In contrast, during extinction, the women with IBS had greater SCR than controls—an effect normalized by administration of a CRF-R1 antagonist. Although the antagonist significantly reduced activity in the thalamus in patients with IBS and controls during acquisition, the drug produced greater suppression of BOLD activity in a wide range of brain regions in IBS patients during extinction, including the medial prefrontal cortex, pons, hippocampus, and anterior insula. CONCLUSION: Although CRF signaling via CRF-R1 is involved in fear acquisition and extinction learning related to expected abdominal pain in patients with IBS and controls, this system appears to be upregulated in patients with IBS. This upregulation might contribute to the previously reported abnormal brain responses to expected abdominal pain.